Avaliação da eficácia, segurança e viabilidade bacteriológica de produtos probióticos utilizados na carcinicultura - Soares, Danyela Carla Elias (2024)
The study aimed to assess the effectiveness of different commercial probiotics used in shrimp farming, evaluating their viability, safety, and impact under various environmental conditions, as well as their contribution to water quality improvement, zootechnical efficiency, and animal health. The study was divided into two chapters comprising four stages. In the first chapter, the initial stage involved gathering information through interviews with shrimp producers on the use and management of commercial probiotics, focusing on usage profiles and effects on culture performance. In the second stage, the primary commercial probiotics mentioned by producers were assessed for the viability of bioactive agents and product safety. In the second chapter, stage three involved isolating and selecting indigenous bacteria from the culture environment to form probiotic consortia. In the fourth and final stage, the effects of these consortia and commercial products on the zootechnical performance of the marine shrimp P. vannamei and water quality were tested in vivo. The results of the first chapter confirm that variations in application protocols and different probiotic usage strategies influence culture parameters, especially animal survival. Although the products were within the limits established by Brazilian regulations, the probiotics analyzed presented lower quantities than those declared on the labels. Of the tested products, only two met the declared bacterial cell count. Additionally, the absence of manufacturer-indicated strains was confirmed in one product, likely reducing its effectiveness and benefits for animal welfare and cultivation. All commercial probiotics analyzed showed high performance variability when exposed to different environmental salinities. In chapter 2, two bacterial consortia with probiotic potential were developed from indigenous bacterial isolates for in vivo application. The selection of bacterial groups for each consortium was based on the desired benefits for the cultured organisms, resulting in two consortia with probiotic potential: one composed of Bacillus species and the other of oxidizing bacteria. The isolation and selection of indigenous probiotic strains contributed to enhanced growth, survival, and biomass performance, in addition to improving water quality. In the in vivo tests, significant differences were observed in the average weight, weekly weight gain, survival, and productivity (kg/ha) of the cultivated shrimp. Among the two indigenous probiotics tested, P6, formulated with oxidizing bacteria, demonstrated higher efficacy in zootechnical performance and water quality, followed by the commercial probiotic P3, composed of Bacillus, Lactobacillus plantarum, Pediococcus acidilactici, and Saccharomyces cerevisiae. The isolated bacteria for the two microbial consortia demonstrated in vitro probiotic properties, such as pathogen inhibition and stress resistance. However, only one strain surpassed the commercial probiotics in the in vivo tests, showing significant effects on survival, growth, and water quality parameters.